Desain Rekayasa Mesin Pemisah Kulit Ari Kedelai Menggunakan Silinder Pengupas Dan Tenaga Blower Kapasitas 15 Kg/jam - Eva Shandy Ratu Aliyyu; Rany Puspita Dewi (Politeknik Negeri Semarang, 2026)
Soybean (Glycine max) is an important food commodity widely used as raw material for tempeh and tofu production. However, the process of peeling and separating soybean skin in small and medium industries is still commonly performed manually, resulting in low efficiency and high processing time. This study aims to design a soybean skin peeling and separating machine using a dry process method with a capacity of 15 kg/hour. The research method used is quantitative, including literature study, numerical calculation, 3D design using SolidWorks, and simulation analysis. The machine utilizes a toothed peeling cylinder driven by a 0.25 HP electric motor and a blower system to separate soybean skin from seeds. The test results showed that the 2 mm gap variation produced the most optimal peeling result with 86% peeled soybeans and 93% intact seeds. The blower operated effectively at approximately 980 rpm with an airflow velocity of 6.76 m/s without causing seed loss. Simulation results showed a maximum stress of 35.74 MPa, displacement of 0.481 mm, and Factor of Safety (FOS) value of 6, indicating that the frame structure is safe for operation. Frequency analysis also confirmed that the machine is safe from resonance during operation. Therefore, the designed machine is considered effective, stable, and suitable for soybean processing in small and medium industries.